2017
DOI: 10.1371/journal.pone.0179670
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of abnormally expressed lncRNAs in colorectal cancer: A meta-analysis

Abstract: BackgroundColorectal cancer (CRC) is the third most prevalent cancer type and the third leading cause of cancer-related deaths worldwide, it is urgently needed to discover a new marker for the progress of CRC. Many long noncoding RNAs (lncRNAs) have been reported to be abnormally expressed in CRC, and may be feasible as effective biomarkers and prognostic factors. The aim of this study was to identify the prognostic value of various lncRNAs in CRC.MethodsPubmed, Web of Science, Embase and Cochrane Library were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…Our results showed that high LncRNA expression was significantly correlated with a poorer prognosis in OS patients, which suggested that LncRNA plays an important role in the prognosis of OS. The same results were also found in the meta-analysis of other cancers such as colon cancer [47], cervical cancer [48] and prostate cancer [49]. However, there was moderate heterogeneity in multivariate analysis of overall survival (I 2 = 54%, P < 0.00001), so we performed meta-regression analysis and subgroup analysis according to race, number of patients, HR availability, cut-off values and NOS scores.…”
Section: Discussionsupporting
confidence: 72%
“…Our results showed that high LncRNA expression was significantly correlated with a poorer prognosis in OS patients, which suggested that LncRNA plays an important role in the prognosis of OS. The same results were also found in the meta-analysis of other cancers such as colon cancer [47], cervical cancer [48] and prostate cancer [49]. However, there was moderate heterogeneity in multivariate analysis of overall survival (I 2 = 54%, P < 0.00001), so we performed meta-regression analysis and subgroup analysis according to race, number of patients, HR availability, cut-off values and NOS scores.…”
Section: Discussionsupporting
confidence: 72%
“… 17 , 18 Previous reviews and meta-analyses have reported the prognostic values of lncRNAs in multiple cancers, such as colorectal cancer, ovarian cancer, prostate cancer, lung cancer, etc. 90 , 91 , 92 , 93 However, no one investigated BC specifically. Since many studies found that dysregulation of multiple lncRNAs may have an impact on the prognosis of BC, we conducted this systematic review to highlight the prognostic values of lncRNAs in BC.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are ~ 22 nucleotides long as compared to 8–10 times longer lncRNAs. The exact functions of lncRNAs are not clear yet but it has been reported that both miRNA and lncRNAs act as regulators for controlling biological processes at post-transcriptional repression of protein-coding genes [ 101 , 102 , 105 ]. Besides,lncRNAs can also act as miRNA sponges and can reduce their regulatory effect on mRNA [ 78 ].…”
Section: Features Of Lncrnamentioning
confidence: 99%
“…Some transcripts of lncRNA including Xist and Kcnq1ot1 are also involved in dosage compensation [ 24 ]. In another report, it has been mentioned that the apoptosis of breast cancer cells can be inhibited by plasmacytoma variant translocation 1 gene (PVT1) [ 101 , 102 , 105 ].…”
Section: Biological Role Of Lncrnas: Association With Diseasesmentioning
confidence: 99%
See 1 more Smart Citation